Association of Coping Strategies and Religiosity With Life Satisfaction of Old People Living in Nursing Homes of Ahvaz City, Iran - Shahla Zahednejhad; Yasin Fazeli; Hossein Rezayi; Mohammad Hossein Haghighizade (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: This study aimed to investigate the association of coping strategies and religiosity with life satisfaction of old people living in nursing homes of Ahvaz City, Iran. Methods & Materials: This was an epidemiological analytical study which was conducted on 100 elderly people (64 male and 36 female) living in nursing homes in Ahvaz. Coping inventory for stressful situations, Allport-Ross religious orientation scale and the satisfacation with life scale which have good reliability and validity were used for data collection. The inclusion criteria included understanding Persian language, having no dementia, willingness to participate in the study, and having at least 60 years of age. The exclusion criteria were having physical or psychiatry disorders, which cause severe depression or anxiety in elderly people, having dementia and not understanding Persian language. For statistical analyses, ANOVA, multivariate regression, and the Pearson correlation coefficient were used. Results: The results showed that there is a significant relationship between coping strategies and religiosity with life satisfaction of old people living in nursing homes (P≤0.05). Conclusion: Coping strategies and religiosity significantly affect life satisfaction of the elderly. Findings of this study could help the nursing homes managers to help elderly people for successful aging through providing religious doctrine and guiding them to choose more efficient solutions to comply with stressors and problems associated with aging.